Sustainable application of coal bottom ash as fine aggregates in concrete: A comprehensive review - Hamada, Hussein Mahmood; Alattar, Alyaa; Tayeh, Bassam; Fadzil, Yahaya; Adesina, Adeyemi (Elsevier Ltd, 2022)
The significant sustainability awareness in the construction industry coupled with the need for the industry to reduce its negative environmental impacts has resulted in the use of various ‎industrial wastes in construction ‎applications such as in the production of concrete. Various industrial wastes can be utilized as ‎partial or total replacements for some components in concrete. Such industrial waste that ‎can be utilized as fine aggregate in the production of concrete is coal bottom ash (CBA). Various studies have utilized CBA as fine aggregate in various types of concrete including high-strength concrete and there has been significant interest in the continuous use of CBA in concrete. To propel more application of CBA in various concrete types and to increase the understanding of the effect of the CBA on the properties of concrete, this comprehensive review was carried out. The properties explored are fresh, mechanical, durability and microstructural properties of concrete incorporating varying proportions of CBA. Findings from the existing studies indicate there exists a significant variation in the impact of CBA on the properties of various concretes. Nonetheless, numerous studies showed that CBA can be utilized as a sustainable alternative to the conventional natural fine aggregates to produce normal and high-strength concrete. Hence, this study recommends carrying out additional studies in this area to evaluate the effect of the physical and chemical properties of CBA on the resulting properties of concrete.